Security in the 21st century: Trends, prospects and challenges - Attuquayefio, P. (University of Ghana, 2015)
Within the social sciences, the concept of security and its implications for policy has attracted considerable attention particularly since the end of the Cold War. At the core of this is a constructivist move geared towards representing security in terms that reflect its contemporary usages. The evolving expansion of the notion of security has engendered policy relevant scholarship on a variety of issues. The panel explores some implications of the expanding conceptualisation of security in the 21st Century focusing on the trends, prospects and challenges. In Breaking the Cybersecurity Dilemma: Balancing National Security and Human Security in Cyberspace, Otoo explores the relevance of human security as a solution to the cybersecurity dilemma that arises as a result of the use of cyberspace as an operational domain for surveillance and cyber warfare. In Interrogating the Concept and Practice of Collective Security Regimes in the 21" Century, Darkwa examines the strengths and limitations of the current international collective security architecture and proffers options for enhancing its utility in addressing contemporary security challenges. In "Hacktivism and its Implications for International Security in the 21" Century'; Oduro Marfo also focuses on the implications of hacker for international security, foreign policy formulation and the theoretical debate in international relations regarding how states behave. In Historicising Security Policy Making in Africa: A Human Security Dimension, Attuquayefio attempts to influence a recalibration of security policy making by tracing the development of security policies in Africa and juxtaposing it by contemporary realities in security consideration. Finally, Appiah assesses the possibility of increased conflicts in sub-Saharan Africa if the regions extractives driven growth is not accompanied with better human development for its growing youthful population in The Chasm between rising Incomes and Human Development and its potential for Conflict in Resource Intensive Countries.
School of social sciences colloquium
Keywords: scholarship; security; Cold War; National Security